2003
DOI: 10.1002/hlca.200390324
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Phase Separation of Racemic and Nonracemic Zwitterionic α‐Amino Acid Amphiphiles in a Phospholipid Environment at the Air/Water Interface: A Grazing‐Incidence X‐Ray Diffraction Study

Abstract: Dedicated to Professor Duilio Arigoni on the occasion of his 75th birthday A grazing-incidence X-ray-diffraction (GIXD) study of the self-assembly, on water, of nonracemic gstearyl glutamic acid (pure or as a mixture with racemic or (S)-1,2-dipalmitoyl-glycero-3-phosphoethanolamine (DPPE)) demonstrated a phase separation of the a-amino acid amphiphile into racemic and enantiomorphous two-dimensional crystallites within the phospholipid domains. The packing arrangements of the two a-amino acid crystalline phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…For the C 18 -TE-Lys system, a possible line-epitaxial crystallization of (S)-C 18 -TE-Lys alongside the racemic crystallites was proposed [19]. However, phase separation of nonracemic amphiphilic a-amino acids within phospholipids is feasible and was detected by GIXD for an appropriate system (see the following article in this issue [26]). The formation of oligopeptides covalently linked to a DPPE molecule indicates that the polycondensation reaction, catalyzed by Ag ions, started at the grain-boundaries between DPPE crystallites and those of the racemic or enantiomorphous amino acid monomers.…”
mentioning
confidence: 99%
“…For the C 18 -TE-Lys system, a possible line-epitaxial crystallization of (S)-C 18 -TE-Lys alongside the racemic crystallites was proposed [19]. However, phase separation of nonracemic amphiphilic a-amino acids within phospholipids is feasible and was detected by GIXD for an appropriate system (see the following article in this issue [26]). The formation of oligopeptides covalently linked to a DPPE molecule indicates that the polycondensation reaction, catalyzed by Ag ions, started at the grain-boundaries between DPPE crystallites and those of the racemic or enantiomorphous amino acid monomers.…”
mentioning
confidence: 99%
“…The air-water interface has been also used for chiral recognition within membrane components [695][696][697][698][699][700] and/or between amphiphile and aqueous guests [701][702][703][704][705][706][707][708]. Mechanical control of chiral recognition was recently achieved using the novel concept of molecular twisting, as shown in figure 79A, where an octacoordinate sodium complex of a polycholesteryl-substituted cyclen embedded at the air-water interface was used as a molecular host [709].…”
Section: Langmuir-blodgett Filmsmentioning
confidence: 99%
“…A polymerization reaction within these crystallites takes place, along the glide plane, between the heterochiral The results of GIXD studies of the packing arrangement of nonracemic amphiphilic α-amino acids have shown that the latter undergo separation, either on pure water or within a monolayer of phospholipids, into a mixture of racemic and enantiomorphous domains [25,32]. Polymerization then takes place within each of the two types of crystallites, yielding syndiotactic peptides in the racemic crystallites and homochiral peptides within the enantiomorphous domains.…”
Section: Isotactic Oligomers Generated Within Monolayers At the Air-wmentioning
confidence: 99%